2011
DOI: 10.1186/1471-2296-12-38
|View full text |Cite
|
Sign up to set email alerts
|

Up-Beat UK: A programme of research into the relationship between coronary heart disease and depression in primary care patients

Abstract: BackgroundCoronary heart disease and depression are both common health problems and by 2020 will be the two leading causes of disability worldwide. Depression has been found to be more common in patients with coronary heart disease but the nature of this relationship is uncertain. In the United Kingdom general practitioners are now being remunerated for case-finding for depression in patients with coronary heart disease, however it is unclear how general practitioners should manage these patients. We aim to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 28 publications
0
32
1
Order By: Relevance
“…Recent studies identified depression and psychological distress as a significant risk factor among patients diagnosed with CHD, which play remarkable role in the development and prognosis of disease (Stafford et al, 2009;Jiang et al, 2002;Chandola et al, 2007;Albus, 2010;Tylee et al, 2011). However, patients from this study had mild depressive symptom and moderate level of psychological distress, which contradict with previous reports.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Recent studies identified depression and psychological distress as a significant risk factor among patients diagnosed with CHD, which play remarkable role in the development and prognosis of disease (Stafford et al, 2009;Jiang et al, 2002;Chandola et al, 2007;Albus, 2010;Tylee et al, 2011). However, patients from this study had mild depressive symptom and moderate level of psychological distress, which contradict with previous reports.…”
Section: Discussioncontrasting
confidence: 56%
“…Studies reported that depression and stress evoke central responses by enhancing the activity of central nervous system and hypothalamic pituitary track which leads to central obesity, insulin resistant, inflammation process, hypertension, platelet activation, and endocrine dysfunction leading to development of CHD (Albus, 2010;Charlson et al, 2011). Moreover, stress and depression were also linked to negative health related behaviors such as low physical activity, poor diet, smoking, and a lack of interest that are also anticipate precursor for CHD (Chandola et al, 2008;Tylee et al, 2011). The literature has also emphasized the role of social factors such as social support and family life and coping in predicting CHD (Albus, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…15 A total of 15 general practices in south London were recruited to the study with a registered population of 150 973 people. Of these, 3325 (2.2%) were on the CHD register, about half of whom had experienced an MI; the remainder had been diagnosed with ischaemic heart disease, usually on the basis of angina.…”
Section: Recruitment and Samplingmentioning
confidence: 99%
“…severity of depressive symptoms in patients with symptomatic CHD. 15 Comparator instruments consisted of three measures of psychological status:…”
Section: How This Fits Inmentioning
confidence: 99%
See 1 more Smart Citation